Association Between Publicly-Funded Contraceptive Services and Abortion Rate in Texas [A39]. (May 2022) - Madison, Anita M.; Powers, Daniel; Maslowsky, Julie; Goyal, Vinita
Abstract : INTRODUCTION: The Texas legislature cut its family planning budget in 2011 and restricted access to abortion in 2013. Our objective was to evaluate how the availability of contraceptive services correlated with a change in the abortion rate before and after these legislative changes. METHODS: We obtained 2010 and 2015 data on contraceptive provision (number of publicly-funded clinics and number of contraceptive clients served) from the Guttmacher Institute and county-level abortion data from Texas Department of State Health Services. We categorized counties by an abortion rate that increased or was less than (low decline) versus greater than or equal to (high decline) the decline seen nationally. We used the chi-square test, t-tests, and logistic regression to evaluate differences in contraceptive provision between high and low abortion decline counties, adjusting for county demographic and health care characteristics. RESULTS: The Texas abortion rate declined by 23% from 2010 to 2015. Statewide, the total number of publicly-funded family planning clinics increased by 11% and total number of contraceptive clients served decreased 4%. Compared to low decline counties (n=79), high decline counties (n=175) had a higher mean number of contraceptive clients served per 1000 women 18-44 years old (51.35 ± 124.26 vs. 81.85 ± 202.66, P <.05) and contraceptive clinics (0.82 ± 1.06 vs. 2.22 ± 5.57, P <.05) in 2015. Abortion decline did not differ by other county characteristics. CONCLUSION: Texas counties with higher abortion rate declines had more publicly-funded contraceptive clinics and served more contraceptive clients than counties with lower declines, demonstrating the importance of greater access to publicly-funded contraceptive services.